Investigation of Traffic Flow Characteristics Parameters in Major National Highways of Bangladesh - Ullah, Mohammad Ahad (Curtin University, 2017)
The research is performed to investigate the detail traffic flow parameters of three major National Highways of Bangladesh. Traffic flow indicators including traffic growth pattern, traffic compositions, directional distribution, truck and bus percentages, seasonal flow variations, weekly and daily flow characteristics, expansion factors, regression models for AADT estimation, and artificial neural network (ANNs) models are analyzed separately for the selected highways in this research work.